2015
DOI: 10.1007/s10096-015-2439-1
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound diagnosis of Clostridium difficile-associated diarrhea

Abstract: Clostridium difficile colitis is diagnosed using an immunoassay or polymerase chain reaction (PCR) assay for toxins A/B. Since ultrasound is frequently used as a screening test for hospitalized patients suffering from different abdominal morbidities, we searched for sonographic indicators of C. difficile infection (CDI). In a prospective and blinded case-control study, abdominal ultrasound was performed on hospitalized patients for whom stool samples were sent for C. difficile toxin immunoassay. All patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Sub-group analysis within the 500+ group µg/g showed that for children where the index FC was related to a new diagnosis of IBD, they were more likely to have abnormal abdominal USSs than if they had an infectious GI condition or subsequent IBD. While abnormalities may be seen in USSs in children with infectious diarrhoea [26][27][28], abdominal USSs carried out on children presenting with diarrhoea, bleeding diarrhoea, or weight loss have positive findings in approximately 20% of cases [29]. In one further study, abnormal USS findings did not distinguish between functional and organic conditions [16].…”
Section: Discussionmentioning
confidence: 85%
“…Sub-group analysis within the 500+ group µg/g showed that for children where the index FC was related to a new diagnosis of IBD, they were more likely to have abnormal abdominal USSs than if they had an infectious GI condition or subsequent IBD. While abnormalities may be seen in USSs in children with infectious diarrhoea [26][27][28], abdominal USSs carried out on children presenting with diarrhoea, bleeding diarrhoea, or weight loss have positive findings in approximately 20% of cases [29]. In one further study, abnormal USS findings did not distinguish between functional and organic conditions [16].…”
Section: Discussionmentioning
confidence: 85%
“…As with most diseases of the GI tract, infection by nontyphoid Salmonella enterica (NTS), referred to as salmonellosis, presents with enterocolitis and symptoms such as abdominal pain, diarrhea, and fever [62][63][64]. Most often, this bacterial infection is acquired through consuming infected foods, primarily consisting of meats, eggs, and dairy products.…”
Section: Salmonellamentioning
confidence: 99%
“…Approximately 20% of IBD patients are diagnosed during their childhood [99,104]. The effects of IBD have long-term impacts on children, namely growth failure or delays in puberty onset [63,100]. In 10-15% of IBD cases, CD and UC cannot be distinguished based on how they present in the patient, who is given an "IBD-unclassified" diagnosis.…”
Section: Irritable Bowel Diseasementioning
confidence: 99%